Design of an Ultra-Low Power RTC for the IoT - David Rosenberger Fernandes Ferrão (2018)
The Internet of Things is growing at an exponential rate. This new perception of reality is being researched even further nowadays because society is starting to develop an interest on these technologies. Market potential is increasing even further, since the foreseeable implementations are diverse and still to be detected. The future applications for the IoT are enthusiastic and they will increase the overall quality of life of the citizens of the world. Developing a component that is crucial for the sustainability of this implementation is the task that truly motivates the intended work for this project. Designing the full-custom circuitry and physical layout of a Real Time Clock becomes a job that has a lot of minor details that need considerable attention. These technicalities truly tone the developers skill and knowledge of different design principles. Besides, developing the solution using subthreshold CMOS techniques will put emphasis on different technological procedures. Producing devices that are heavily dependent on PVT variations, operational frequency and power consumption define this new task, that needs a stable approach to all these diverse figure of merits, even though they are all interconnected. The study and understanding of these different approaches allows for a more complex in depth grasp of this recent intriguing proceedings.